2018
DOI: 10.21873/anticanres.12674
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure–Cytotoxicity Relationship of 2-(N-cyclicamino)chromone Derivatives

Abstract: Abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…Human OSCC cell lines (Ca9-22, derived from gingival tissue; HSC-2, HSC-3. HSC-4, derived from tongue) and human normal oral mesenchymal cells (HGF, HPLF, HPC) at 10-18 population doubling levels were cultured at 37˚C in DMEM supplemented with 10% heat-inactivated FBS, 100 units/ml, penicillin G and 100 μg/ml streptomycin sulfate under a humidified 5% CO 2 atmosphere, as described previously (20,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Human OSCC cell lines (Ca9-22, derived from gingival tissue; HSC-2, HSC-3. HSC-4, derived from tongue) and human normal oral mesenchymal cells (HGF, HPLF, HPC) at 10-18 population doubling levels were cultured at 37˚C in DMEM supplemented with 10% heat-inactivated FBS, 100 units/ml, penicillin G and 100 μg/ml streptomycin sulfate under a humidified 5% CO 2 atmosphere, as described previously (20,21).…”
mentioning
confidence: 99%
“…After 48 h, the medium was replaced with fresh medium containing (1/2) 2 serially diluted test compounds. Cells were incubated for 48 h and the relative viable cell number was then determined in triplicate by MTT method, as described previously (20,21). Control cells were treated with the same amounts of DMSO and the cell damage induced by DMSO was subtracted.…”
mentioning
confidence: 99%
“…Their tumor specificity was also significantly positively correlated lipophilicity, 3D shape, and negative charge (p-values from 1.45×10 -6 to 3.18×10 -8 ) (Figure 6). Taken together, these data suggest that ANTICANCER RESEARCH 38: 4459-4467 (2018) 4466 When we compared the A series of compounds of 3-(Ncyclicamino)chromones (this study) with their structural isomers, 2-(N-cyclicamino)chromones (13), there were common properties: 4-phenyl-1-piperazinyl derivatives (3a) of both groups had the highest cytotoxicity against four human OSCC cell lines, followed by 4-phenyl-1-piperidinyl derivatives (2a) in both cases [ Table I and (13)]. Furthermore, TS of both groups of compounds were correlated with 3D structure (mass or shape) reflected by Mor17v, Mor17m and Mor22m for 2-(Ncyclicamino)chromones, and FCASA-, Chi_G/D, VE3sign_G, J_D/Dt for 3-(N-cyclicamino) chromones.…”
Section: Discussionmentioning
confidence: 70%
“…We recently reported that 7-methoxy-2-(4-morpholinyl)-4H-1-benzopyran-4-one [5c which had the highest tumor specificity among 15 2-(N-cyclicamino)chromone derivatives (13)], led to cytotoxic growth inhibition in OSCC cell lines without induction of apoptosis. These results suggest that these structural isomers, 2-(N-cyclicamino)chromones and 3-(N-cyclicamino)chromones, have no apoptosis-inducing activity, despite exhibiting different modes of growth inhibition (either cytotoxic or cytostatic).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation